PHYSICO-CHEMICAL PROPERTIES OF SORBENT BASED ON POLYVINYLCHLORIDE PLASTIC (Scientific journal of the Fergana State University, 2023)
The purpose of the study Is to study the physicochemical properties of a new polyvinyl chloride-based sorbent. The research is based on the fact that experimental results were obtained using modern methods such as thermogravimetric analysis, differential thermal analysis, complexonometry. The ionic equilibrium between the sorbent and the sorbate is deduced from the Langmuir and Freundlich isotherm models, using the equations used in modern theories of sorption thermodynamics. The study of the physicochemical properties of PVC-based ion exchangers revealed that they have high thermal stability and high absorption of metal ions.